A Feasibility Study of Bio-Briquettes Production from the Skin and Epidermis Layer of Cassava (Manihot esculenta) as An Alternative Energy - Neda Prasiska Kusumawati; Dodyk Pranowo; Dian Siswanto; Wresti L. Anggayasti (Postgraduate, University of Mataram, 2024)
Unprocessed leftover cassava wastes from the home industries in Pomahan Village in Bojonegoro, East Java, has become a serious problem as a pollutant to the environment. This study examined the quality of bio-briquettes made from cassava skin waste with its epidermis starch as an adhesive agent, or binder. The aim is to assess the quality of the bio-briquettes for alternative energy sources and their suitability from an economic point of view. The utilized research method was a descriptive quantitative approach by measuring water and ash content, calorific value test, and economic feasibility calculation. The results indicated that the highest calorific value of 5337.83 cal/g was obtained from a bio-briquette mix of 50 g cassava skin with 5% epidermis starch binder. This bio-briquette also possesses the lowest water and ash contents of 2.75 and 8%, respectively, compared to other mixtures. The economic feasibility calculation showed a BEP value of 423 kg/ month, B/C Ratio of 6.14-fold, ROI of 30%, and PBI of 0.2 years. In conclusion, cassava-based bio-briquettes are economically promising and environmentally friendly due to their biomass property and help to tackle the environmental problem due to the cassava waste.